Upaya Peningkatan Pemasaran Digital melalui Pendampingan Pengelolaan Website di Desa Wisata - Vikaliana, Resista; Irawan, Ade; Iskandar, Yelita Anggiane (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Assistance in managing the Alamendah Tourism Village website in Bandung Regency is carried out to overcome challenges in tourism promotion which still relies on conventional methods. With the development of digital technology, effective website management has become an urgent need to increase the competitiveness of tourist destinations. This program is designed to provide technical skills to village communities in managing websites as an effective promotional tool. Assistance is provided through a combination of online and offline methods, including storytelling training, SEO optimization, content maintenance, and integration with social media. This activity succeeded in increasing participants' understanding of digital technology and providing direct benefits in optimizing the potential of village websites. The evaluation showed very positive results, with participants finding the activity relevant, useful and satisfying. However, several website elements such as the navigation bar, responsive design, and accessibility still need to be improved. Suggestions are given to continue ongoing assistance, improve website features, and carry out regular evaluations to ensure program sustainability. With this approach, the Alamendah Tourism Village is expected to be able to increase its attractiveness and visibility as a leading ecotourism destination, as well as encourage community independence in managing digital marketing.